From Vision to Venture: Enterprise Architecture in Odisha’s Educational Landscape - Nayak, Niladri Bihari (Digital Repository of Theses - SSBM Geneva, 2025)
The educational landscape in Odisha, an Eastern state in India, can be reshaped through a value-based education enterprise architecture framework, focusing on transforming vision into venture. By integrating value streams to align Technology, Education, Culture, and business strategies, the state aims to create a cohesive and adaptive educational environment. The purpose of this research is to reshape Odisha's educational landscape through a robust value-based education enterprise architecture framework. This approach addresses existing challenges such as disparities in literacy rates and high dropout rates by optimizing resource allocation and streamlining processes. The guiding ethical standards and values-based innovation frameworks ensure that the transformation is both sustainable and ethically grounded, fostering a culture of continuous improvement and adaptability. The methods employed in this initiative involve integrating value streams to align technology, education, culture, and business strategies. Key initiatives such as the 5T (Teamwork, Transparency, Technology, Time, Transformation) High School Transformation Program and Entrepreneurship Development Programs (EDPs) are instrumental in this transformation. The research anticipates several outcomes. These programs focus on modernizing educational infrastructure, incorporating advanced technological tools, and providing entrepreneurship education to train and motivate youth. By enhancing learning environments with cutting-edge tools and technologies, these initiatives create a conducive atmosphere for innovation and critical thinking. Continuous capacity-building programs for educators and administrators ensure that the educational workforce is well-equipped to support these changes. The integration of enterprise architecture in Odisha's education system is poised to create a robust framework that supports lifelong learning and entrepreneurial success, particularly in K-12 education. By fostering partnerships between government, industries, and academic institutions, the state aims to build a collaborative ecosystem that nurtures budding entrepreneurs. The establishment of Livelihood Business Incubation Centres and other strategic initiatives further supports this vision, ensuring that students are well-prepared to navigate and thrive in a rapidly evolving global landscape.